Physical attributes of a Dystroferric Red Latosol (Oxisol) under different management systems - Pinto, Leandro Campos; Chagas, Wantuir Filipe Teixeira; Amaral, Francisco Hélcio Canuto (Revista Agrogeoambiental, 2019)
The relationship of management and soil quality may be evaluated by the behavior of soil physical, chemical and biological properties. In the assessment of soil structure, it is sought attributes in the view of measuring the porosity and the distribution of pores by size and its implication to permeability and rigidity of the pores, as well as the stability of the units that composes soil structure. The aim of this research was to assess the structure of a Dystroferric Red Latosol (Oxisol) under conventional corn crop, conventional coffee crop, eucalyptus crop and an equilibrium reference (native vegetation), by the determination of the particle density, bulk density, calculated total porosity, microporosity, macroporosity, moisture saturation, determined total porosity, blocked pores and aggregated stability. Soil under native vegetation presented the lowest values of particle density, probably due to the greatest soil organic matter content in this environment. It was verified a tendency of increasing blocked pores and decreasing bulk density. As expected, bulk density varied from 0.87 to 1.03 g cm-3, showing an inversely proportional distribution related to total porosity. The largest values of geometric mean diameter presented by the soil under native vegetation are due to the greater structuration degree of this soil, which contributes to the stabilization of the aggregates in this environment. The native vegetation environment presented a better soil physical quality in relation to other land uses.